1996
DOI: 10.1083/jcb.134.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Armadillo is required for adherens junction assembly, cell polarity, and morphogenesis during Drosophila embryogenesis.

Abstract: Abstract. Morphological and biochemical analyseshave identified a set of proteins which together form a structure known as the adherens junction. Elegant experiments in tissue culture support the idea that adherens junctions play a key role in cell--cell adhesion and in organizing cells into epithelia. During normal embryonic development, cells quickly organize epithelia; these epithelial cells participate in many of the key morphogenetic movements of gastrulation. This prompted the hypothesis that adherens ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
258
2
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 295 publications
(272 citation statements)
references
References 51 publications
9
258
2
3
Order By: Relevance
“…The Drosophila cadherin also interacts with catenins, and it is likely that these interactions are also modulated during invertebrate morphogenetic events such as embryonic development. Evidence supporting this hypothesis has been reported by two groups, demonstrating the requirement of the Drosophila ␤-catenin homolog Armadillo for the formation of Drosophila adherens junction and epithelial polarity (28,29).…”
Section: Discussionsupporting
confidence: 64%
“…The Drosophila cadherin also interacts with catenins, and it is likely that these interactions are also modulated during invertebrate morphogenetic events such as embryonic development. Evidence supporting this hypothesis has been reported by two groups, demonstrating the requirement of the Drosophila ␤-catenin homolog Armadillo for the formation of Drosophila adherens junction and epithelial polarity (28,29).…”
Section: Discussionsupporting
confidence: 64%
“…Another difference between shg and arm mutants was that the mis-positioning of the germ cells occurred only in the latter. A similar disarrangement of cells was also observed in the embryonic epithelia of intermediate alleles of arm (Cox et al 1996;Müller & Wiechaus 1996). These arm phenotypes cannot necessarily be explained by a simple loss of cell-cell adhesion, leading us to propose a distinctive role of Armadillo in the cadherin/catenin adhesion system.…”
Section: Roles For De-cadherin and Armadillo In The Cadherin/catenin supporting
confidence: 64%
“…In other models of branching morphogenesis, it has been suggested that the epithelia reverts to a mesenchymal state during branching [64]. Canonical signaling could be mediating such a transition in the kidney, although this would be contrary to other data, where a loss of β-catenin is correlated with epithelialto-mesenchymal transition [65]. It is possible that Wnt signaling is simply mediating differential adhesiveness between the tips and the stalk, perhaps through regulating the expression or activity of a cell adhesion molecule.…”
Section: Pathway Usage In Renal Vesicle Formationmentioning
confidence: 87%